PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII.A SMP NEGERI 10 TAPUNG - Desvia Uvita Putri; Titi Solfitri; Suhermi Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractThe research was classroom action research that aims to improve mathematics learning outcomes with applied cooperative learning model of type Team Games Tournament. The subject of the research is students of class VIII.A in SMP Negeri 10 Tapung in the first semester academic years 2013/2014. There are 24 students in the class, consist of 12 boys and 12 girls who have heterogeneous academic ability. The research are two cycles. Each a cycle has four stages, the stages are planning, implementation, observation, and reflection. Each end of the cycle of daily test tournament carried out. The success of action was characterized by learning process that was better and the improvement of the number of students who reach minimum completeness criteria on a daily test tournament at the end of each cycle compared to the number of students who reach minimum completeness criteria on score basic.The results of this research showed an improvement in the learning process of each meeting and each cycle. In addition, the results also showed an improvement of the number of students who reach minimum completeness criteria on Tournament I and Tournament II compared the number of students who reach minimum completeness criteria on score basic. Thus , this research shows that the application of cooperative learning model of type Team Games Tournament can improve mathematics learning outcomes of the studentsof class VIII.A in SMP Negeri 10 Tapung.Key Words : Mathematics Learning Outcomes, Cooperative Learning, Team Games Tournament, Classroom Action Research